(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Geopolitics of the conclave. The intertwining of politics and religion in a sacred rite This paper retraces the history of episcopal elections, highlighting their evolution from a purely religious event into one laden with political implications. Politics influences the Church both ad intra, because it is itself a social institution, and ad extra, stemming from its historical interaction with temporal powers. The external political influence is exemplified by the ius exclusivae exercised by Catholic states, formally abolished at the beginning of the twentieth century. The elimination of the right of veto, however, has not freed the Pope’s election from political pressures, given that he is a global leader and wields undeniable transnational political authority. The essay illustrates these aspects, explaining how the last conclave was influenced by both the reforms enacted by Benedict XVI and the evolving geopolitics of the College of Cardinals under Pope Francis. This demonstrates how papal succession is also a question of continuity/discontinuity regarding the political action (internal and external) exercised by the previous pontiff. Finally, the paper highlights how the election of Cardinal Robert F. Prevost (Leo XIV) is a consequence of these dynamics, which point less to the identification of a specific person and more to the selection of a religiously and politically capable profile that can ensure both continuity and discontinuity. SOMMARIO: 1. Introduzione - 2. Premesse storiche - 3. Religione e politica nelle elezioni senza conclave - 4. L’istituzionalizzazione del conclave e il diritto di veto degli Stati cattolici - 5. Continuità e discontinuità: le interferenze politiche tra passato e presente - 6. La riforma del conclave di Benedetto XVI - 7. Geopolitica del conclave del 2025 - 8. Conclusione (e post-scriptum).